TINJAUAN KEMAMPUAN TEKNIK DASAR BERMAIN SEPAKBOLA PADA PEMAIN USIA 16 TAHUN DI KECAMATAN BANGKO - Alam, Nurayatul; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this study was to determine the level of basic technical skills in playing football in 16 year old players in Bangko District. This research belongs to the type of descriptive research, which is a study that aims to get a real picture or reality of the state of the object of research supported by data in the form of numbers obtained from the results of data collection, namely by using the method of test and measurement techniques. The place of this research was carried out in Koni field, Rokan Hilir Regency, Jl. Main, the Koni alley. This research was conducted for 6 months from June 2020 to March 2021. Based on the results of the study, it can be concluded that the basic technical skills of playing football in 16-year-old players in Bangko District, after being tested using four different techniques in soccer games, namely passing and stoping. , dribbling, heading and shooting. with the results obtained are in the